Maternal and neonatal morbidity in relation to the instrument used for mid‐cavity rotational operative vaginal delivery: a prospective cohort study. Issue 12 (7th August 2013) - Bahl, R; Van de, M; Macleod, M; Strachan, B; Murphy, DJ
<x xml:space="preserve">Abstract</x> Objective To compare the maternal and neonatal morbidity associated with alternative instruments used to perform a mid‐cavity rotational delivery. Design A prospective cohort study. Setting Two university teaching hospitals in Scotland and England. Population Three hundred and eighty‐one nulliparous women who had a mid‐cavity rotational operative vaginal delivery. Methods A data collection sheet was completed by the research team following delivery. Main outcome measures Postpartum haemorrhage, third‐ and fourth‐degree perineal tears, low cord pH, neonatal trauma, and failed or sequential operative vaginal delivery. Results One hundred and sixty‐three women (42.8%) underwent manual rotation followed by non‐rotational forceps delivery, 73 (19.1%) had a rotational vacuum delivery, and 145 (38.1%) delivered with the assistance of rotational (Kielland) forceps. The rates of postpartum haemorrhage were similar when comparing manual rotation with rotational vacuum (adjusted OR 1.42, 95% CI 0.66–3.98), and when comparing manual rotation with Kielland forceps (adjusted OR 1.22, 95% CI 0.71–2.88). The results were comparable for third‐ and fourth‐degree perineal tears (adjusted OR 0.85, 95% CI 0.13–1.89; adjusted OR 0.94, 95% CI 0.39–1.82), low cord pH (adjusted OR 1.76, 95% CI 0.44–6.91; adjusted OR 1.12, 95% CI 0.44–2.83), neonatal trauma (adjusted OR 0.50, 95% CI 0.16–1.55; adjusted OR 3.25, 95% CI 0.65–16.17), and admission to the neonatal intensive care unit (adjusted OR 1.47, 95% CI 0.45–4.81; adjusted OR 1.04, 95% CI 0.49–2.19). The sequential use of instruments was less likely with manual rotation and forceps than with rotational vacuum delivery (0.6 versus 36.9%, OR 0.01, 95% CI 0.002–0.090). Conclusions Maternal and perinatal outcomes are comparable with Kielland forceps, vacuum extraction, and manual rotation, with few serious adverse outcomes. With appropriate training mid‐cavity rotational delivery can be practiced safely, including the use of Kielland forceps.